Aurally impressed, yet not more stressed: On the relationship between audiovisual realism, social anxiety, and presence in a virtual social stress scenario - Sarah Roßkopf; Andreas Mühlberger; Felix Stärz; Matthias Blau; Steven van de Par; Leon O. H. Kroczek (PLoS ONE, 2026)
Binaural auralizations can create spatial hearing impressions that closely resemble real sound sources, enhancing immersion and realism in virtual environments. Although social interactions often involve emotional responses such as stress (e.g., during a job interview), the interplay between emotion and binaural auralizations in virtual social interactions remains underexplored. Therefore, we investigated the effects of audiovisual realism in a virtual social stress scenario based on the Trier Social Stress Test. Acoustic realism was manipulated between subjects using head-tracked binaural auralizations and a diotic condition. For binaural auralizations, simulated binaural room impulse responses were based either on individual or generic head-related impulse responses. Stressfulness was also varied: a control group performed a task with reduced cognitive demand and social-evaluative threat by only “testing” a virtual job interview scenario and reading aloud preformulated answers. Social presence, stress responses (measured by salivary cortisol, heart rate, and self-reports), and gaze behavior were assessed in 78 participants. The virtual scenario reliably induced stress across all audio conditions compared to the control version. Binaural auralizations were rated as more externalized and realistic than diotic audio, but did not significantly influence social presence, stress responses, or gaze behavior. Social presence increased with higher social-evaluative threat and over time. Social anxiety was associated with greater social presence, altered gaze behavior (shorter latencies), and, to some extent, stronger stress responses. It also interacted with the auralization type in affecting social presence. Overall, enhancing acoustic realism with externalized auralizations did not affect stress or presence in the virtual scenario. Elevated stress levels also in the control condition may have masked potential audio effects, implicating the need for investigating binaural auralizations in less stress-related social contexts.